Linking the morphology and ecology of subtidal soft-bottom marine benthic habitats: A novel multiscale approach. (5th June 2020) - Mestdagh, Sebastiaan; Amiri-Simkooei, Alireza; van der Reijden, Karin J.; Koop, Leo; O'Flynn, Sarah; Snellen, Mirjam; Van Sluis, Christiaan; Govers, Laura L.; Simons, Dick G.; Herman, Peter M.J.; Olff, Han; Ysebaert, Tom
Abstract: High-resolution surveying techniques of subtidal soft-bottom seafloor habitats show higher small-scale variation in topography and sediment type than previously thought, but the ecological relevance of this variation remains unclear. In addition, high-resolution surveys of benthic fauna show a large spatial variability in community composition, but this has yet poorly been linked to seafloor morphology and sediment composition. For instance, on soft-bottom coastal shelves, hydrodynamic forces from winds and tidal currents can cause nested multiscale morphological features ranging from metre-scale (mega)ripples, to sand waves and kilometre-scale linear sandbanks. This multiscale habitat heterogeneity is generally disregarded in the ecological assessments of benthic habitats. We therefore developed and tested a novel multiscale assessment toolbox that combines standard bathymetry, multibeam backscatter classification, video surveying of epibenthos and box core samples of sediment and macrobenthos. In a study on the Brown Bank, a sandbank in the southern North Sea, we found that these methods are greatly complementary and allow for more detail in the interpretation of benthic surveys. Acoustic and video data characterised the seafloor surface and subsurface, and macrobenthos communities were found to be structured by both sandbank and sand wave topography. We found indications that acoustic techniques can be used to determine the location of epibenthic reefs. The multiscale assessment toolbox furthermore allows formulating recommendations for conservation management related to the impact of sea floor disturbances through dredging and trawling. Highlights: Soft-sediment seafloors exhibit multi-scale morphological features. Combining multibeam sonar, video footage and grab samples increases survey detail. Animal communities are structured by both sandbank and sand wave topography. Occurrence of reefs can be estimated via acoustic techniques.